Primeira maturação sexual, crescimento e bioquímica sanguínea de Pacamã ( Lophiosilurus alexandri, Steindachner, 1876) em condições controladas - REINALDO MELILLO FILHO (2020)
This work aimed to evaluate the growth, size and age of first maturation, hormonal levels and biochemical parameters of Lophiosilurus alexandri. Four hundred juveniles produced at the UFMG Aquaculture Laboratory were used. After completing 90 days after hatching (DAH), the growth stage began, where the animals were followed up to 968 DAH. During the experiment, successive sampling of males and females were performed for histological analysis of the gonads, monitoring growth, measurement of hepatosomatic (IHS) and gonadosomatic (IGS) indices. From the macroscopic differentiation of the gonads, blood was collected at 372, 481, 845 and 968 DAH for biochemical analysis. Hormonal analyzes (Estradiol, Testosterone and 17α-hydroxyprogesterone) were performed at 845 and 968 DAH, when macroscopically developed gonads were detected. The data obtained were always compared between males and females of the same age and for individuals of the same sex at different ages. There was no difference for growth in weight and length between males and females (P> 0.05). Completely mature males were found at 593 DAH, with 29.88 ± 1.76 cm and 444.1 ± 77.03 g. The females reached advanced maturity at 845 DAH, with 36.51 ± 1.06 cm and 783.05 ± 48.57 g. All hormones evaluated were at similar levels between males and females at 845 DAH (P> 0.05). However, at 968 DAH there was an increase in the level of E2 in females, also differing from the value found for males at this time (P <0.05). For testosterone, at 968 DAH a higher level of this hormone was recorded in females (P <0.05). Biochemical data showed little difference between sex. Biochemical data showed little difference between genders. Male fish showed higher values of alanine aminotransferase (ALT) in 372 DAH, magnesium at 481 DAH and triglycerides at 372 DAH and 481 DAH, (P <0.05), however most of the biochemical data analyzed varied significantly (P <0, 05) for individuals of the same sex at different ages. Only lactate dehydrogenase (LDH) for females showed no variation (P> 0.05). The results of the present work provide basic and essential information for the future of fisheries management and for the commercial production planning of L. alexandri.